Preliminary Study of Renal Hemodynamic Alteration in Early Childhood Diabetes Mellitus. (February 2013) - Wacharasindhu, Suttipong; Rugpolmuang, Rottanat; Roonghiranwat, Thapana; Supornsilchai, Vichit; Sahakitrungruang, Taninee; Aroonparkmongkol, Suphab; Chaiwatanarat, Tawatchai
<x xml:space="preserve">Abstract</x> Renal hemodynamic study was performed in eight patients associated with type 1, early childhood diabetes mellitus (DM) and seven patients associated with type 2, early childhood DM. The results in both types of DM revealed a significant reduction in peritubular capillary flow and a high value of glomerular filtration rate (GFR) in the presence of reduced renal perfusion characteristic of glomerular hyperfiltration. These findings imply that renal ischemia has already developed in both types of early stage childhood DM and GFR is overestimated in DM, which may mislead to improper interpretation of renal function.